Metabolic engineering to enhance the accumulation of bioactive flavonoids licochalcone A and echinatin in Glycyrrhiza inflata (Licorice) hairy roots - Wu, Zhigeng; Singh, Sanjay Kumar; Lyu, Ruiqing; Pattanaik, Sitakanta; Wang, Ying; Li, Yongqing; Yuan, Ling; Liu, Yongliang (Frontiers in Plant Science, 2022)
Echinatin and licochalcone A (LCA) are valuable chalcones preferentially accumulated in roots and rhizomes of licorice (Glycyrrhiza inflata). The licorice chalcones (licochalcones) are valued for their anti-inflammatory, anti-microbial and antioxidant properties and have been widely used in cosmetic, pharmaceutical, and food industries. However, echinatin and LCA are accumulated in low quantities, and the biosynthesis and regulation of licochalcones have not been fully elucidated. In this study, we explored the potential of a R2R3-MYB transcription factor (TF) AtMYB12, a known regulator of flavonoid biosynthesis in Arabidopsis, for metabolic engineering of the bioactive flavonoids in G. inflata hairy roots. Overexpression of AtMYB12 in the hairy roots greatly enhanced the production of total flavonoids (3-fold), echinatin (2-fold) and LCA (5-fold). RNA-seq analysis of AtMYB12-overexpressing hairy roots revealed that expression of phenylpropanoid/flavonoid pathway genes, such as phenylalanine ammonia-lyase (PAL), chalcone synthase (CHS) and flavanone 3'-hydroxylase (F3'H), are significantly induced compared to the control. Transient promoter activity assay indicated that AtMYB12 activates the GiCHS1 promoter in plant cells, and mutation to the MYB-binding motif in the GiCHS1 promoter abolished activation. In addition, transcriptomic analysis revealed that AtMYB12-overexpression reprograms carbohydrate metabolism likely to increase carbon flux into flavonoid biosynthesis. Further, AtMYB12 activated the biotic defense pathways possibly by activating the salicylic acid and jasmonic acid signaling, as well as by upregulating WRKY TFs. The transcriptome of AtMYB12-overexpressing hairy roots serves as a valuable source for identification of potential candidate genes involved in LCA biosynthesis. Taken together, our findings suggest that AtMYB12 is an effective gene for metabolic engineering of valuable bioactive flavonoids in plants.